Williams obstetrics - Cunningham, F. Gary (McGraw-Hill, 2018)
Williams Obstetrics is the most detailed, comprehensive, and rigorously referenced text on the subject. Written by an author team from the world-renowned University of Texas Southwestern, the hallmarks of this classic are its thoroughness, scientific basis, and practical applicability for the obstetrician at the bedside. Presented in full color, the Twenty-Fifth Edition is enhanced by more than 1,000 full color illustrations, and an increased focus on maternal-fetal medicine, one of the largest subspecialties of ob-gyn. Readers will also appreciate an improved, more logical content flow for an improved reading experience.